Dinamika Akumulasi Kadmium Pada Tanaman Kangkung Darat (Ipomoae reptans Poir) - Liong, Syarifuddin; Noor, Alfian; Taba, Paulina; Zubair, Hazirin (Indonesia Chimica Acta, 2009)
ne heavy metal, which is potential as pollutant, is cadmium that has been accumulated in soil and sediment. Although, cadmium is non essential element for plants, it is easily adsorbed and accumulated by various plants. The negative effect of cadmium on plants is that it can prevent the absorption of nutrition so that the plant growth will be inhibited and then the plant will die. Therefore, it is necessary to reduce the concentration of cadmium to be used as good growth media. Several methods of heavy metal accumulation, such as physical, chemical and biological methods, have been used, but the three methods have been considered as less effective methods. The use of plants to accumulate heavy metals in polluted soil is considered as a good method because the method is a safe method and can increase the soil fertility. In this research, accumulation of cadmium has been conducted by using Ipomeae reptans Poir. Result showed that the highest concentration that can be accumulated by I. reptans Poir was 3317.68 mg/kg of dried mass with the plantation time of 21 days. The increase of concentration in the growth media increased the cadmium concentration accumulated. The high accumulation of cadmium showed that I. reptans Poir is a hyperaccumulator plant for cadmium. The bioconcentration value was higher than 1, whereas the translocation factor was lower than 1 indicating that the accumulation mechanism was phytostabilization.Keywords : cadmium, accumulation, analysis, Ipomoae reptans Poir.Â